2012
DOI: 10.1021/ac302960j
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MALDI Tandem Mass Spectrometric Imaging of Cocaine from Brain Tissue with a Deuterated Internal Standard

Abstract: Mass spectrometric imaging (MSI) is an analytical technique used to determine the distribution of individual analytes within a given sample. A wide array of analytes and samples can be investigated by MSI, including drug distribution in rats, lipid analysis from brain tissue, protein differentiation in tumors, and plant metabolite distributions. Matrix-assisted laser desorption/ionization (MALDI) is a soft ionization technique capable of desorbing and ionizing a large range of compounds, and it is the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 29 publications
5
141
0
Order By: Relevance
“…Pirman et al reported some studies in which the contents of small molecules in brain tissue sections were determined by quantitative MALDI-MS/MS imaging using the same stable isotope dilution technique and discussed about the origin of a false-positive signal. 10,11) It concluded that the similar false-positive signal in the tissue section was the non-labeled target drug with no significant contribution from impurity of the stable isotopic standard. Similarly in our case, the false-positive blank signal in the mouse blood vessel and kidney sections was partially derived from an impurity of deuterated CAD in the same manner, although it was not the same as MALDI matrix in their study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pirman et al reported some studies in which the contents of small molecules in brain tissue sections were determined by quantitative MALDI-MS/MS imaging using the same stable isotope dilution technique and discussed about the origin of a false-positive signal. 10,11) It concluded that the similar false-positive signal in the tissue section was the non-labeled target drug with no significant contribution from impurity of the stable isotopic standard. Similarly in our case, the false-positive blank signal in the mouse blood vessel and kidney sections was partially derived from an impurity of deuterated CAD in the same manner, although it was not the same as MALDI matrix in their study.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some groups demonstrated that the quantitative analysis by MALDI imaging MS/MS using a stable isotopic internal standard enabled us to determine contents of small DOI: 10.5702/massspectrometry.A0021 molecules in animal tissue sections. [10][11][12] By the incorporation of a uniformly applied internal standard coupled with the specificity of MS/MS technique and scan-by-scan ionsignal normalization, the quantitative MALDI imaging was improved in a tissue section.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a stable isotope-labeled version of the target drug is considered ideal for the normalization of ion suppression. 24) In this study, we used S-777469-d 10 , a deuterium-labeled version of S-777469, as an internal standard to maximize the quantitative capability of MALDI-IMS, and uniformly coated S-777469-d 10 solution over the sections to allow pixel-by-pixel normalization (Figs. 3c and f).…”
Section: Quanti Cation Of S-777469 In Tissue Sections By Maldi-imsmentioning
confidence: 99%
“…[22][23][24] e preparation of analyte calibration standards is also a key factor for successful quanti cation because analyte extraction from tissue sections into the matrix solution should be considered. 16) Several studies on MALDI-IMS method development for the quanti cation of small molecule drugs have been reported in the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ganglioside classes, which are defi ned by the carbohydrate head group, MS also allows profi ling of ganglioside lipoforms ( 15 ) with different structure of acyl chain and sphingoid base. Ganglioside quantifi cation is applied to ganglioside pattern investigation ( 16 ) in food analyses ( 17,18 ), but is also used in the analysis of lysosomal storage diseases ( 19 ) and in quantitative imaging MS ( 20 ). Lysogangliosides play a role in the pathogenesis of gangliosidoses.…”
mentioning
confidence: 99%